2002
DOI: 10.1177/000348940211100104
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Lateralization of the Paralyzed Vocal Cord without Tracheostomy

Abstract: The initial management of bilateral abductor vocal cord paralysis is usually tracheostomy. It is proposed that a reversible endoscopic vocal cord lateral fixation would avoid this morbid procedure. The operation is performed by laryngoscopy utilizing the endo-extralaryngeal suture technique of Lichtenberger. Two polypropylene sutures are looped over one of the paralyzed vocal cords and brought out through the neck skin. A small incision is made, and the sutures are secured in the sternohyoid muscle. If movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
1
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 16 publications
0
51
1
3
Order By: Relevance
“…Suture lateralization of a VF can be performed as a temporary measure to improve the airway during the period after injury where long-term outcome is uncertain. 238 Permanent treatments include posterior transverse cordotomy or arytenoid reduction and removal procedures. 239 SLN paralysis and paresis are more difficult to both recognize and treat.…”
mentioning
confidence: 99%
“…Suture lateralization of a VF can be performed as a temporary measure to improve the airway during the period after injury where long-term outcome is uncertain. 238 Permanent treatments include posterior transverse cordotomy or arytenoid reduction and removal procedures. 239 SLN paralysis and paresis are more difficult to both recognize and treat.…”
mentioning
confidence: 99%
“…In described group 9 patients underwent tracheostomy procedure only one was without it. Lichtenberger suggested that endoscopic vocal cord lateral fixation would avoid the need for tracheostomy in cases of bilateral vocal cord paralysis [10]. But in our group in 5 cases unilateral laterofixation of vocal cord was unsuccessful as a first stage of surgical treatment of bilateral vocal cords.…”
Section: Discussionmentioning
confidence: 55%
“…A key advantage to early laterofixation is avoidance of a tracheostomy in patients with acute bilateral vocal fold paralysis [19,[21][22][23]. In 1993, Ejnell and Tisell [21] introduced the concept of acute temporary laterofixation for the treatment of bilateral vocal cord paralysis as an alternative to tracheostomy.…”
Section: Early Versus Late Laterofixationmentioning
confidence: 99%